2021
DOI: 10.3389/fmars.2021.773734
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Mechanisms Underlying Hypoxia-Tolerant Mitochondrial Phenotype During Hypoxia-Reoxygenation Stress in a Marine Facultative Anaerobe, the Blue Mussel Mytilus edulis

Abstract: Hypoxia is common in marine environments and a major stressor for marine organisms inhabiting benthic and intertidal zones. Several studies have explored the responses of these organisms to hypoxic stress at the whole organism level with a focus on energy metabolism and mitochondrial response, but the instrinsic mitochondrial responses that support the organelle’s function under hypoxia and reoxygenation (H/R) stress are not well understood. We studied the effects of acute H/R stress (10 min anoxia followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 105 publications
1
6
0
Order By: Relevance
“…Our study also revealed that species-specific differences were more strongly associated with oxidative stress status, whereas metabolic indices and nitrosative stress parameters were more relevant to the response to hypoxia-reoxygenation. These findings support the idea that antioxidant protection may have a limited role in gibel carp and that other mechanisms, such as metabolic adjustments, molecular chaperones, or protein quality-control mechanisms, may be more important ( Falfushynska et al, 2016 ; Sokolov et al, 2021 , 2019 ; Zhang et al, 2012 ). However, it is important to note that our study only examined two closely related species of cyprinids, limiting the scope for evolutionary or adaptive conclusions.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study also revealed that species-specific differences were more strongly associated with oxidative stress status, whereas metabolic indices and nitrosative stress parameters were more relevant to the response to hypoxia-reoxygenation. These findings support the idea that antioxidant protection may have a limited role in gibel carp and that other mechanisms, such as metabolic adjustments, molecular chaperones, or protein quality-control mechanisms, may be more important ( Falfushynska et al, 2016 ; Sokolov et al, 2021 , 2019 ; Zhang et al, 2012 ). However, it is important to note that our study only examined two closely related species of cyprinids, limiting the scope for evolutionary or adaptive conclusions.…”
Section: Discussionsupporting
confidence: 82%
“…The adaptive physiological responses of hypoxia-tolerant organisms to oxygen fluctuations rely heavily on mitochondrial adjustments ( Bickler and Leslie, 2007 ; Pamenter, 2014 ; Sokolova et al, 2019 ). While hypoxia-sensitive species experience mitochondrial respiration collapse during reoxygenation, hypoxia-tolerant species exhibit robust or enhanced mitochondrial respiration following an H/R cycle, which is essential for restoring energy homeostasis during recovery ( Adzigbli et al, 2022a , b ; Buck and Pamenter, 2006 ; Ivanina et al, 2016 ; Pamenter, 2014 ; Sokolov et al, 2021 ). However, this increased respiration can lead to the production of ROS and potential oxidative stress during hypoxia and reoxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…Reoxygenation stress after periods of anoxia or hypoxia is a common major stressor for intertidal marine species but also for aquaculture species that are emersed for transportation to their farm or market destinations. Intertidal bivalves are naturally adapted to cope with reoxygenation during high tide by stimulating antioxidant enzymes [46][47][48][49] and metabolic adjustments [50][51][52][53]. Bivalves also respond behaviourally (i.e., valve closure) when exposed to unfavourable conditions such as increasing temperatures or emersion.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that acclimation to high salinity reduces the intrinsic mitochondrial plasticity to acute anoxia stress, which is observable in the mitochondria of low-salinity-acclimated oysters. Intrinsic plasticity of isolated mitochondria in response to various stimuli depends on mechanisms such as post-translational protein modifications ( Falfushynska et al, 2020b ; Mathers and Staples, 2019 ; Pagliarini and Dixon, 2006 ; Sokolov et al, 2021 ; Yang and Gibson, 2019 ), allosteric regulation of enzyme activity ( Acin-Perez et al, 2011 ; Beauvoit and Rigoulet, 2001 ; Cherkasov et al, 2007 ) and proton-motive force-dependent regulation of respiration and ROS production ( Brand, 2000 ; Jastroch et al, 2010 ; Lambert and Brand, 2004 ). In our present study, the exact mechanisms responsible for the differences in the intrinsic mitochondrial plasticity between the mitochondria of oysters acclimated to high and low salinity could not be determined requiring further investigation.…”
Section: Discussionmentioning
confidence: 99%